Selection of potential reference genes for RT-qPCR in the plant pathogenic fungus Colletotrichum fructicola - Chen, Xingzhou; Chen, Xinggang; Tan, Qian; He, Yuan; Wang, Zhikai; Zhou, Guoying; Liu, Junang (Frontiers in Microbiology, 2022)
Colletotrichum is widespread, and these pathogenic fungi can cause various plant diseases. Studies have shown that Colletotrichum fructicola causes oil-tea (Camellia oleifera) anthracnose and is widely distributed as a dominant fungus in all Ca. oleifera-producing regions. Real-time quantitative PCR(RT-qPCR) is considered the most reliable technique for simultaneously measuring relative gene expression levels in different tissues. Target genes are typically quantified using RT-qPCR to explore gene function, and reliable RT-qPCR results require data normalization using stable reference genes. No studies have reported a suitable reference gene in C. fructicola. This study has 8 candidate reference genes (CfCk, CfRpp, CfUce, CfRrp, CfAdrh, CfDd, CfAct, CfTub) were selected from C. fructicola-Ca. oleifera transcriptome data and evaluated and sequenced using geNorm, NormFinder, and Bestkeeper algorithms. The results showed that CfRrp showed better stability in C. fructicola, both during the growth of pure pathogenic fungi and during the invasion of different oil-tea leaves. After normalization with CfRrp, the differentially expressed target genes were similar to the transcriptome. Our work provides suitable reference genes for future studies to quantify target gene expression levels in C. fructicola.